Biodiversitas ikan Amfidromus Gobiidae di Perairan Indonesia - Salindeho, Indra R. N. (e-Journal BUDIDAYA PERAIRAN, 2021)
Gobiidae fish are distributed widely in tropical and subtropical waters, and inhabit almost all benthic habitats ranging from freshwater, intertidal to offshore, with varied substrates such as muddy bottom, rocky, and coral beds. The diets of Gobiidae varies greatly, from microalgae to small fish. The life cycle follows the amphidromus migration pattern, the mature Gobiidae spawn in fresh water and the hatched larvae drift to brackish waters or to the sea, and will return to fresh water in a few weeks or months later. Species of Gobiidae varies greatly in Indonesian waters. The species composition of Gobiid fish schooling varies greatly by location and by seasonal appearance in estuary waters.